Island Constraints and Adjunct & Argument Asymmetry in Turkish - Sinan Çakır (Dilbilim Araştırmaları Dergisi)
Due to the adjunct & argument asymmetry in Turkish, the interpretation of argument wh-words within island structures does not result in ungrammaticality while that of wh-adjuncts results in ungrammaticality (Özsoy 1996, Arslan 1999, Görgülü 2006, Çakır 2015). Yet, the following questions are still unanswered: (1) When there are not any intervening islands in the interpretation of wh-words that originate in lower CPs, do we obtain the same results? (2) Is the observed different behavior of wh-elements a result of a more general adjunct-argument asymmetry that is indifferent to island effects? In the present study, the data were obtained through a Grammaticality Judgment Test containing 36 interrogative sentences from 435 participants. According to the results, the island constraints hold in Turkish, at least, for the sentence-level wh-adjuncts. However, it was also observed that there exists a general adjunct & argument asymmetry in Turkish which is valid for all complex sentences no matter they are subject to island effects or not.